Application of the Role Playing Method for Indonesian Language Subjects in MI Grade 2 - Nur Aini (Universitas Muhammadiyah Sidoarjo, 2018)
Role playing can be called a drama or imitating certain behaviors or characters that differentiate each student's position. With this method, students are expected to be able to issue their imagination in playing a character or living up to the character of a predetermined character. The research was conducted on 2nd grade students at MI Muhammadiyah 2 Kedungbanteng Tanggulangin, Sidoarjo. Method of role play a method that can be one of the solutions in the learning process in the classroom that allows learners or students the spirit in learning. And it can increase students learning interest so that students can sharpen their thinking to learn well and try hard to get a satisfactory value.